Participatory Approach in Decision Making Processes for Water Resources Management in the Mediterranean Basin - Carlo Giupponi; Jaroslav Mysiak; Jacopo Crimi (Fondazione Eni Enrico Mattei (FEEM), 2006)
This paper deals with the comparative analysis of different policy options for water resources management in three south-eastern Mediterranean countries. The applied methodology follows a participatory approach throughout its implementation and is supported by the use of three different software packages dealing with water allocation budget, water quality simulation, and Multi Criteria Analysis, respectively. The paper briefly describes the general objectives of the SMART project and then presents the three local case studies, the valuation objectives and the applied methodology - developed as a general replicable framework suitable for implementation in other decision-making processes. All the steps needed for a correct implementation are therefore described. Following the conceptualisation of the problem, the choice of the appropriate indicators as well as the calculation of their weighting and value functions are detailed. The paper concludes with the results of the Multi Criteria and the related Sensitivity Analyses performed, showing how the different policy responses under consideration can be assessed and furthermore compared through case studies thanks to their relative performances. The adopted methodology was found to be an effective operational approach for bridging scientific modelling and policy making by integrating the model outputs in a conceptual framework that can be understood and utilised by non experts, thus showing concrete potential for participatory decision making.
Keywords: Q01; Q25; Q28; Q5; 330; Scientific Advice; Policy-Making; Participatory Modelling; Decision Support